Deciphering Macrophage Phenotypes upon Lipid Uptake and Atherosclerosis - Lee, Jihye (Immune Netw, 2020)
In the progression of atherosclerosis, macrophages are the key immune cells for foam cell formation. During hyperlipidemic condition, phagocytic cells such as monocytes and macrophages uptake oxidized low-density lipoproteins (oxLDLs) accumulated in subintimal space, and lipid droplets are accumulated in their cytosols. In this review, we discussed the characteristics and phenotypic changes of macrophages in atherosclerosis and the effect of cytosolic lipid accumulation on macrophage phenotype. Due to macrophage plasticity, the inflammatory phenotypes triggered by oxLDL can be re-programmed by cytosolic lipid accumulation, showing downregulation of NF-κB activation followed by activation of anti-inflammatory genes, leading to tissue repair and homeostasis. We also discuss about various in vivo and in vitro models for atherosclerosis research and next generation sequencing technologies for foam cell gene expression profiling. Analysis of the phenotypic changes of macrophages during the progression of atherosclerosis with adequate approach may lead to exact understandings of the cellular mechanisms and hint therapeutic targets for the treatment of atherosclerosis.